Penerapan Konsep Green infrastructure dalam Mencegah Erosi di Kawasan Sub Das Cikapundung: Studi Kasus : Kecamatan Lembang - Annisa Yulianti Suhana; Hilwati Hindersah (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Phenomena that often occur in watershed areas include sedimentation and erosion. Sedimentation often occurs in downstream watershed areas while erosion often occurs in the upstream area of a watershed. The Cikapundung Sub-Watershed located in Lembang District is the upstream area of the Cikapundung watershed itself. In addition, the Lembang Area also has soil types that are prone to soil movement. These two things, which are the Cikapundung Sub-Watershed area in Lembang District, are considered to have the potential for erosion. Erosion can be prevented with green infrastructure. Green infrastructure has many types, one of which is soil bioengineering which is a soil engineering technique that is considered capable of preventing and reducing the rate of soil erosion. Soil bioengineering utilizes living plants, namely vetiver grass so that it does not have a negative impact on the environment. The analysis carried out in this erosion prevention study by determining the prediction of erosion rates using the GIS-based USLE model. The analysis was carried out in two stages, namely the analysis of the prediction of erosion rates with assumptions without the application of green infrastructure and the second is the analysis of the effectiveness of the application of green infrastructure. The results showed that before the existence of conservation and land management measures, the total amount of predicted land erosion rate was 44,580.11 Tons / Ha / Year with very light - heavy qualifications. However, after analyzing the effectiveness of green infrastructure soil bioengineering by converting the weight of land management to 0.4, namely the conservation weight of vetiver grass, Lembang District can eliminate a maximum of 19.160 tons / ha / year or 42,97% and change the qualification of erosion hazard levels to very low - low. Abstrak. Fenomena yang sering terjadi di kawasan DAS diantaranya adalah sedimentasi dan erosi. Sedimentasi sering terjadi di kawasan DAS bagian hilir sedangkan erosi sering terjadi di kawasan hulu dari suatu DAS. Sub DAS Cikapundung yang berada di Kecamatan Lembang merupakan kawasan hulu dari DAS Cikapundung itu sendiri. Selain itu, Kawasan Lembang juga memiliki jenis tanah yang rawan pergerakkan tanah. Kedua hal ini yang menjadi kawasan Sub DAS Cikapundung di Kecamatan Lembang dinilai memiliki potensi erosi. Erosi dapat dicegah dengan green infrastructure. Green infrastructure memiliki banyak jenisnya salah satunya adalah soil bioengineering yang merupakan teknik rekayasa tanah yang dinilai mampu mencegah dan mengurangi laju erosi tanah. Soil bioengineering memanfaatkan tanaman hidup yaitu rumput vetiver sehingga tidak berdampak negatif terhadap lingkungan. Analisis yang dilakukan dalam penelitian pencegahan erosi ini dengan menentukan prediksi laju erosi menggunakan model USLE berbasis SIG. Analisis dilakukan secara dua tahap pertama yaitu analisis prediksi laju erosi dengan asumsi tanpa penerapan green infrastructure dan kedua yaitu analisis efektivitas penerapan green infrastructure. Hasilnya menunjukkan bahwa sebelum adanya tindakan konservasi dan pengelolaan lahan, total besaran prediksi laju erosi lahan adalah 44.580,11 Ton/Ha/Tahun dengan kualifikasi sangat ringan – berat. Namun setelah dianalisis keefektivitasan green infrastructure soil bioengineering dengan mengkonversi bobot pegelolaan lahan menjadi 0,4 yaitu bobot konservasi rumput vetiver, Kecamatan Lembang dapat menghilangkan maximum 19.160 ton/ha/tahun atau 42,97% dan mengubah kualifikasi tingkat bahaya erosi menjadi sangat rendah – rendah saja